MENINGKATKAN PARTISIPASI BELAJAR SISWA MELALUI MODEL PEMBELAJARAN PBL PADA SISWA KELAS IV SDN 17/I RANTAU PURI PADA PEMBELAJARAN IPAS - Wulandari, Yunita; Fauziah, Sobrini; Mayang Sari, Nara; Sri Wahyuni, Endang; Destrinelli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This classroom action research is an effort to increase student learning participation in science learning using the Problem Based Learning (PBL) model. Based on the pre-cycle scores, it is known that of the 24 students there were only 6 students who met the score > KKM (75) while 18 of them had the score < KKM (75). Based on the scores in cycle 1 of my material and my needs, it is known that of the 24 students there were only 12 students who met the score > KKM (75) while 12 of them had the score < KKM (75). If examined carefully, this score of 75 was only obtained by a small number of students in the class. So if it is a percentage, it is very far below the specified percentage of total student completion, namely 75% of the total number of students. For this reason, it is very necessary to improve the deficiencies in cycle I learning through the implementation of cycle II actions. Based on the scores in cycle 2 of the material on how do I meet my needs, it is known that of the 24 students there are only 17 students who meet the score > KKM (75) while 7 of them have the score < KKM (75).